Tea and other diet-related practices in relation to sleep health in midlife women from Mexico City: qualitative and quantitative findings - Zamora, Astrid N.; Roberts, Elizabeth F. S.; Sharp, Lilian; Borra, Catherine; Lee, Jennifer; Téllez-Rojo, Martha M.; Peterson, Karen E.; Torres-Olascoaga, Libni A.; Cantoral, Alejandra; Jansen, Erica C. (Frontiers in Sleep, 2024)
Purpose Little is known regarding women's lived experiences of how diet impacts sleep. Based on ethnographic interviews among working-class women from Mexico City, our primary aim was to identify themes related to diet and sleep among midlife women. Informed by qualitative analyses, a secondary aim was to examine associations between tea and sleep duration in a broader cohort. Materials and methods We conducted a cross-sectional study that entailed in-depth ethnographic interviews about sleep and other behaviors, including diet, with a purposive sample of 30 women from the ELEMENT cohort. Ethnographer field notes and transcripts were analyzed using thematic analysis. Guided by findings from the interviews demonstrating that tea consumption might be associated with sleep, we conducted post-hoc analyses of the relationship between tea and sleep duration using data from food frequency questionnaires and actigraphy, respectively, in the broader cohort (n = 406). Results The mean (SD) age of the ethnographic sample was 50.0 (9.0) years. The top noted theme was the use of herbal tea (in Spanish infusion) to improve sleep; most women (29/30) discussed herbal teas, characterizing them as a “natural remedy” to facilitate sleep. The mean (SD) age of the broader sample (N = 406) was 48.4 (6.2) years. Post-hoc analyses revealed positive associations between tea without sugar (though not necessarily herbal tea) and sleep duration. We found that every serving of tea without sugar consumed was associated with an 18.0 min per night [β (SE) = 18.0 (7.8); p = 0.022] and a 13.4 min per night [β (SE) =13.4 (5.6); p = 0.017] increase in weekend and 7-day sleep duration, respectively. Conclusions Within a sample of 30 midlife women, dietary practices were described in relation to sleep, specifically the consumption of herbal teas to promote sleep.